1999
DOI: 10.1046/j.1365-3040.1999.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen deprivation on cell division and expansion in leaves of Ricinus communis L.

Abstract: The effects of nitrogen deprivation on leaf extension, cell numbers and epidermal cell size were followed in leaves of Ricinus communis L. The extent to which reductions in final cell number or final epidermal cell size contributed to the reduction in final leaf size depended on the developmental stage of the leaf at the time of N deprivation. In leaves which already had their full complement of cells (leaf 2), the reduction in final leaf size following nitrogen deprivation was associated with a reduction in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 35 publications
7
54
0
Order By: Relevance
“…A large effect of nitrogen on cell division was observed in a dicot Ricinus communis provided that nitrogen starvation was initiated early in leaf development, in the period of intense cell division (Roggatz et al 1999). Our data showed that nitrogen allocated to the uppermost internode (peduncle) and flag leaf contributed in their increased size with higher supply of nitrogen.…”
Section: Nitrogen Application At Vegetative Stage and Leaf Characterimentioning
confidence: 56%
“…A large effect of nitrogen on cell division was observed in a dicot Ricinus communis provided that nitrogen starvation was initiated early in leaf development, in the period of intense cell division (Roggatz et al 1999). Our data showed that nitrogen allocated to the uppermost internode (peduncle) and flag leaf contributed in their increased size with higher supply of nitrogen.…”
Section: Nitrogen Application At Vegetative Stage and Leaf Characterimentioning
confidence: 56%
“…It is known from cellular studies of tobacco that the final organ and cell size is dependent on nutrient availability (Walter and Schurr, 2005). In contrast to our plants, the reduction of final leaf size is always pronounced as a reduction of final cell size and, depending on the stage of development when the nitrogen limitation occurs, a concomitant reduction of the numbers of cells (Roggatz et al, 1999).…”
Section: Reduced Growth Is Established As Slower Growth Rates and Is mentioning
confidence: 66%
“…The leaf size been largely a result of cell production and cell expansion. However, Roggatz et al [18] demonstrated that the effect of nitrogen deficiency depends on the developmental status of the leaf when nitrogen stress is imposed. Deprivation of nitrogen in the earlier stages of leaf development when cell division still taking place resulted in greater reduction in final leaf size.…”
Section: Resultsmentioning
confidence: 99%